A Suspicious Discipline: The chair of natural law and nations in the eyes of catholic legal culture - Olivares Jatib, Oscar; Pérez Godoy, Fernando (Cuadernos de Historia del Derecho, 2025)
The discipline of natural law and law of nations has been the subject of academic and intellectual controversy throughout Western Europe since the seventeenth century. In this context, the present study asks about the effects of the European confessional division on legal education and literature dominated by the ius commune. As we try to prove, the Catholic intellectual culture and its Protestant counterpart were interconnected through a space for the circulation, communication and translation of legal knowledge created by the European legal science. It is concluded that the authors and works of rational natural law, although they collided at different dogmatic points with the Catholic legal culture, foster continental legal education with new methodological proposals and theories in the field of the rising public law.
Keywords: natural law; legal culture; more geometric; censorship; confessional división